Los modelos de mujer y las sexualidades disidentes en las novelas de Lucía Etxebarria Amor, curiosidad, prozac y dudas y Beatriz y los cuerpos celestes - Kobiela-Kwaśniewska, Marta (Romanica Silesiana)
The Women’s Models and Alternative Sexuality in the Novels of Lucía Etxebarria Love, Curiosity, Prozac and Doubts and Beatrice and the Heavenly Bodies The main aim of this article is to present ways in which a controversial Spanish novelist, Lucía Etxebarria, expresses and subverts traditional social models and sexual identity of Spanish women at the end of the twentieth century by creation of female protagonists such as a promiscuouos girl, a workaholic executive or a housewife that tend to deconstruct socially normative conceptualizations of their roles and sexuality and they search for alternative constructions of feminine identity, both social and sexual one. It seems that a lesbian model of relationship is alternative to a monogamous compulsory heterosexuality. Key words: Spanish feminine literature, women’s sexual identity, lesbian model, Lucía Etxebarria.